“Green gold” - “Divine gift” – “The definition of family”: Perceptions and attitudes of domestic olive tourism visitors regarding the olive heritage in Greece - Maria Kouri; Marios Kondakis (Via@)
Despite the longstanding significance of olive heritage in Greece, research on olive tourism (OT) remains sparse. This study aims to explore the OT demand-side aspects of OT in Greece, by examining the perceptions and attitudes of domestic OT visitors. Qualitative interviews were conducted with a random sample of 55 predominantly domestic OT visitors from February to April 2023, as part of the Olive4All European project. The findings indicate that domestic OT visitors are highly educated, possessing substantial awareness of the olive’s multifaceted significance. Nonetheless, visits to olive sites markedly enhance visitors’ comprehension of the olive’s sociocultural, environmental and economic aspects, and are, therefore, highly appreciated. Consequently, olive sites should provide comprehensive educational content addressing these dimensions, emphasising environmental and financial aspects, as well as the lesser-known qualities of the olives/olive oil. This approach aligns with the expectations and needs of the knowledgeable domestic market, promotes special interest tourism, and ultimately contributes to safeguarding the olive heritage.